2012
DOI: 10.1016/j.jjcc.2012.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between left ventricular ejection fraction and mitral annular displacement derived by speckle tracking echocardiography in patients with different heart diseases

Abstract: The specificity in the correlation between STE-derived MAD and LVEF was found in patients with each heart disease, which should be taken into account when assessing these parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 29 publications
3
22
0
Order By: Relevance
“…S′ has a limitation of angle dependency which can be measured only in the ultrasound beam direction. In comparison of TMAD and S′ in various cardiac diseases and normal controls, previous reports recommended the use of TMAD for the evaluation of longitudinal systolic function …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S′ has a limitation of angle dependency which can be measured only in the ultrasound beam direction. In comparison of TMAD and S′ in various cardiac diseases and normal controls, previous reports recommended the use of TMAD for the evaluation of longitudinal systolic function …”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Reduced GLS has been shown as a predictor of long-term LV dysfunction after MV surgery in patients with organic MR. [9][10][11][12] However, measurement of GLS requires analysis of three apical views with good visualization of all the LV segments. Application of speckle-tracking technology to the mitral annulus provides a quick assessment of tissue-tracking mitral annular displacement (TMAD) at the lateral, septal, and midpoint between these portions of the mitral annulus relative to the apex during one cardiac beat [15][16][17][18][19] and can be performed more rapidly than GLS. 17,18 TMAD has been reported to be a sensitive and reproducible method for assessment of longitudinal systolic function, and it does not depend on endocardial definition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 However, this method is highly dependent on image quality. [26][27][28] Thus, we attempted to apply this technique to the lateral and septal tricuspid annulus for the assessment of RV systolic dysfunction. Several studies have shown that this method can be used for the assessment of left ventricular systolic dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that this method can be used for the assessment of left ventricular systolic dysfunction. [26][27][28] Thus, we attempted to apply this technique to the lateral and septal tricuspid annulus for the assessment of RV systolic dysfunction. This STE technique provides tracking of the midpoint of tricuspid annular plane displacement, which reflects not only lateral but also septal annular wall motion without angle dependence.…”
Section: Introductionmentioning
confidence: 99%